Haiti : Use of Fund Resources-Request for Emergency Post-Conflict Assistance. (IMF Staff Country Reports; Country Report, 2005)
This paper discusses the Use of IMF Resources in Haiti and Request for Emergency Post-Conflict Assistance (EPCA). The EPCA-supported program was on track until May 2005. All end-December and end-March targets were observed, inflation declined, the exchange rate stabilized, and net international reserves were increased. However, following expansionary fiscal and monetary policies during May-June, most end-June targets were missed. Also, while many structural measures were implemented as envisaged, progress on key structural measures, including the census of public employment and domestic arrears, was delayed.